The Oho'o Langka Tradition in the Luhu State Community of West Seram Regency - Dokolamo, Hamid (Universitas Pattimura, 2023)
The Langka Oho’o Tradition is a Tradition that has existed since ancient times. The background of the Langka Oho’o Tradition in Luhu Country is a tradition that has existed since the time of the ancestors by the people of Luhu Country. But in practice, The Langka Oho’o Tradition has undergone a slight change, namely that nowadays, cloth/sarong is no longer used as clothing or clothing, and kris is a tool to carry out the langka Oho’o Tradition. The problem of this research is to know the process of implementing the langka Oho’o Tradition to the people of Luhu Country. Thus, this study aims to determine the Implementation Process and Langka Oho’o Tradition in Luhu Country, Huamual District, West Seram Regency. The method used in this study is qualitative research using a descriptive approach. The results of this study indicate that the Langka Oho’o tradition takes place every year on Eid al-Fitr until seven days. The value of the Langka Oho’o Tradition for the people of Luhu Country is to commemorate Eid Al-Fitr and strengthen friendships among the people of Luhu Country.